2012
DOI: 10.1590/s0100-40422012000700004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de ICP OES com configuração axial ou radial para determinação de iodo em sal de cozinha

Abstract: Recebido em 8/5/11; aceito em 23/2/12; publicado na web em 15/6/12 EVALUATION OF ICP OES WITH AXIAL OR RADIAL VIEWS FOR DETERMINATION OF IODINE IN TABLE SALT.The performance of inductively-coupled plasma optical emission spectrometers with axial and radial views for determination of iodine in table salt was evaluated. Interference and memory effects in nitric acid and water-soluble tertiary amines (CFA-C) media were studied. Based on a factorial experiment, one optimum instrument operational condition for axia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In Brazil, 93% of iodine salt samples sold to the public were found to contain 15-45mg/kg iodine, with most containing 20-30mg/kg (9). Analyses of table salt samples obtained in towns near the city where this study was conducted, showed average levels of iodine of 22-27mg/kg of salt (10,11). Thus, for this study, each gram of salt was considered to contain 25μg of iodine.…”
Section: Prevalence Of Iodine Intake Inadequacy In Elderly Brazilian mentioning
confidence: 86%
“…In Brazil, 93% of iodine salt samples sold to the public were found to contain 15-45mg/kg iodine, with most containing 20-30mg/kg (9). Analyses of table salt samples obtained in towns near the city where this study was conducted, showed average levels of iodine of 22-27mg/kg of salt (10,11). Thus, for this study, each gram of salt was considered to contain 25μg of iodine.…”
Section: Prevalence Of Iodine Intake Inadequacy In Elderly Brazilian mentioning
confidence: 86%
“…46 Non-spectral interferences for iodine determination have also been the subject of studies investigating interferences caused in sample introduction. The effect of acidic solution has been reported, and memory effects mainly attributed to the formation of HI and I 2 are well-known, 42,[50][51][52][53][54] including memory effects due to the vessels used for sample preparation. 52 Based on previous reports, the use of diluted ammonia solutions or water-soluble tertiary amines for dilution of samples and standards as well as for washing the nebulization system prevents memory effects for iodine.…”
Section: Required Features Of Sample Preparation For Further Halogen ...mentioning
confidence: 99%
“…52 Based on previous reports, the use of diluted ammonia solutions or water-soluble tertiary amines for dilution of samples and standards as well as for washing the nebulization system prevents memory effects for iodine. 42,[50][51][52][53][54] According to the authors' experience, careful optimization of the concentration of solution as well as the time needed for washing is dependent on the residual matrix compounds and on the iodine concentration in the samples. A detailed study has shown the effect of the solvent type and iodine form (iodide or iodate) on the total iodine determination in milk powder and human serum by ICP-MS. 7,53,55 It was observed that iodide was prone to more pronounced memory effects in acidic solutions (0.14 mol L À1 HNO 3 ) than iodate is.…”
Section: Required Features Of Sample Preparation For Further Halogen ...mentioning
confidence: 99%